2009
DOI: 10.1063/1.3130742
|View full text |Cite
|
Sign up to set email alerts
|

Rippling instability on surfaces of stressed crystalline conductors

Abstract: We report a surface morphological stability analysis for stressed, conducting crystalline solids without and with the simultaneous application of an electric field based on self-consistent dynamical simulations according to a fully nonlinear model. The analysis reveals that in addition to a cracklike surface instability, a very-long-wavelength instability may be triggered that leads to the formation of secondary ripples on the surface morphology. We demonstrate that the number of ripples formed scales linearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[13][14][15] Furthermore, the morphological evolution of a thin epitaxial film grown on a deformable substrate has been analyzed. 16 In previous studies, 17,18 we have demonstrated that surface electromigration due to a sufficiently strong and properly applied external electric field can inhibit the ATG instability and prevent surface cracking of stressed elastic conductors. We have also demonstrated that a sufficiently strong and properly directed electric field can inhibit the SK instability in a heteroepitaxial film/substrate system and stabilize the planar surface morphology of a coherently strained epitaxial film.…”
mentioning
confidence: 98%
“…[13][14][15] Furthermore, the morphological evolution of a thin epitaxial film grown on a deformable substrate has been analyzed. 16 In previous studies, 17,18 we have demonstrated that surface electromigration due to a sufficiently strong and properly applied external electric field can inhibit the ATG instability and prevent surface cracking of stressed elastic conductors. We have also demonstrated that a sufficiently strong and properly directed electric field can inhibit the SK instability in a heteroepitaxial film/substrate system and stabilize the planar surface morphology of a coherently strained epitaxial film.…”
mentioning
confidence: 98%